Carsick - Waters, John 1946- (Corsair, 2015)
The visual artist behind such cult films as "Hairspray" traces his haphazard cross-country hitchhiking journey at the sides of a motley group of unsuspecting drivers, including a gentle farmer, an indie band, and the author's unexpected hero. --Publisher's description